Cooperation or Non-cooperation? An Attempt to Conceptualize Economic Sanctions in Global Political Conflicts (KULT_online, 2019)
The book Coercive Economic Sanctions and International Conflicts: A Sociological Theory by Mark Daniel Jaeger examines the social conditions within sanctions conflicts that lead either to cooperation or non-cooperation. The main assumption of the work is that coercive economic sanctions should be understood as relational, socially constructed facts and that conflicts over sanctions, as discursive conflicts, result from incompatibilities of interest (issue conflicts) or identity (identity conflicts). Based on the premises of Luhmann’s social systems theory and securitization theory, the author creates a theoretical model that seeks to explore the conflicts’ (de-)escalation from a sociological perspective. The study is based on case studies of sanctions conflicts between Mainland China and Taiwan as well as between the US and Iran over the Islamic Republic’s nuclear program. The research has demonstrated that depending on the combination of different sanctions regimes (positive or negative) and particular sanctions policies of an initiator and the response of an addressee, the conflict may result in further securitization or de-securitization.